Curable composition and composite material

By using polar monomers and organic ions to organicize the layered compound in the monomer raw material, the problem of poor dispersion in the prior art is solved, and good dispersion of the layered compound and low moisture permeability and high transparency of the composite material without the need for organic solvents and ultrasonic treatment are achieved.

CN119790082APending Publication Date: 2025-04-08NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380061609.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2023-08-17
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art Without using organic solvents and ultrasonic treatment, it is difficult to achieve good dispersion of layered compounds in the resin matrix, resulting in a decrease in dispersion.

Method used

The layered compounds organically formed by adding polar monomers and organic ions to the monomer raw material, the layered compounds are well dispersed in the liquid phase by using the polar monomers in these monomer raw materials, and cured by light and heat.

Benefits of technology

Good dispersion of the layered compound in the cured substance without the need for organic solvents and ultrasonic treatment is achieved, reducing environmental load and improving productivity, while obtaining composite materials with low moisture permeability and high transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

Provided is a curable composition in which a layered compound is dispersed in a liquid phase containing a monomer raw material. Provided is a curable composition comprising: a liquid phase comprising a monomer raw material; and a layered compound dispersed in the liquid phase. The layered compound is a layered compound which is organized using an organic ion. The monomer raw material contains a polar monomer (m1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable composition and a composite material formed from the curable composition.

[0002] This application claims priority based on Japanese Patent Application No. 2022-134093 filed on August 25, 2022, and the entire contents of this application are incorporated herein by reference. Background Art

[0003] It is known that there are composite materials formed by dispersing layered compounds such as layered clay minerals in a matrix phase containing a resin material. For example, Patent Document 1 states: In order to provide an acrylic adhesive or an adhesive sheet thereof that can take into account both transparency and adhesive properties at high temperatures, an organic layered clay mineral and a polymerization initiator are mixed with an organic solvent in an acrylic monomer, and a suitable external agent is added to the mixture, and the above-mentioned monomer, polymerization initiator and part of the organic solvent are inserted between the layers of the organic layered clay mineral, and then the solvent is removed and a polymerization reaction is carried out, thereby obtaining a composite in which the above-mentioned clay mineral is finely dispersed in the generated polymer (paragraphs 0005 to 0006). As other documents related to adhesives containing acrylic polymers and organic layered clay minerals, Patent Document 2 can be cited.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-129020

[0007] Patent Document 2: Japanese Patent Application Publication No. 2003-183457 Summary of the invention

[0008] Problems to be solved by the invention

[0009] Patent documentation 1 discloses in order to obtain the curable composition of the fine dispersion of organic layered clay mineral and in the presence of organic solvent, carries out ultrasonic treatment or the processing of high-speed shear type dispersion device, and dispersibility is reduced (comparative example 2) when organic solvent is not used. In addition, in the specific example recorded in patent documentation 2, after utilizing dispersion machine to mix, ultrasonic treatment is further carried out, thus transparent (good dispersibility) dispersion liquid (paragraph 0047 of patent documentation 2) is prepared. If it is provided that can be prepared in the case of not needing organic solvent, ultrasonic treatment and can form the curable composition of the solidified material that layered compound is well dispersed in the matrix phase comprising resin material, then it is useful from the viewpoint of alleviating environmental load, improving productivity.

[0010] The present invention is made in view of the above situation, and one of its purposes is to provide a curable composition in which a layered compound is dispersed in a liquid phase containing a monomer raw material. Another purpose of the present invention is to provide a composite material as a cured product of the curable composition. Another related purpose is to provide a method for producing the curable composition.

[0011] Means used to solve problems

[0012] According to the present specification, a curable composition is provided, the curable composition comprising: a liquid phase containing a monomer raw material; and a layered compound dispersed in the above-mentioned liquid phase. The above-mentioned layered compound is a layered compound (hereinafter, also referred to as layered compound (A)) that has been organicized using organic ions. The above-mentioned monomer raw material contains a polar monomer (m1). By using a polar monomer (m1), it is easy to disperse the above-mentioned layered compound (A) in the liquid phase containing the polar monomer (m1). By curing the curable composition, a cured product in which the above-mentioned layered compound (A) is well dispersed in the matrix phase formed by the above-mentioned liquid phase can be formed.

[0013] In some embodiments of the technology disclosed herein (including a curable composition, a method for producing the same, a composite material as a cured product of the curable composition, an adhesive sheet or a laminated sheet having the composite material, etc., and the same applies hereinafter), the monomer raw material preferably contains a polar monomer containing a nitrogen atom (m1 N ) (hereinafter sometimes referred to as "nitrogen-containing monomer (m1 N )" or "monomer (m1 N )". Nitrogen-containing monomer (m1 N ) can preferably contribute to the improvement of the dispersibility of the layered compound (A).

[0014] In some embodiments, the monomer raw material contains a (meth)acrylic acid chain alkyl ester (m2) having a chain alkyl group with 4 to 20 carbon atoms at the ester terminal (hereinafter also referred to as "monomer (m2)". The technology disclosed herein can be preferably implemented by using a monomer raw material containing monomer (m2). The content of the monomer (m2) in the monomer raw material can be, for example, 55% by weight or more.

[0015] In some embodiments, the monomer raw material comprises a (meth)acrylic acid chain alkyl ester (m2 L ) (hereinafter also referred to as "monomer (m2 L The technology disclosed herein can be achieved by using a monomer (m2 L ) of the monomer raw materials.

[0016] In some embodiments, the curable composition may further include a softener. By using the monomer raw material and the softener in combination, the properties of the cured product (eg, flexibility, optical properties) can be appropriately adjusted.

[0017] Some forms of curable compositions are configured to form adhesives by curing by at least one of light and heat. Here, as described above, "adhesive" refers to a material that is in a soft solid (viscoelastic) state within a temperature range near room temperature and has the property of being adhered to an adherend by pressure. According to such a curable composition, an adhesive in which a layered compound (A) is dispersed in a matrix phase of a viscoelastic material from a liquid phase of the curable composition can be easily formed.

[0018] According to the present description, a composite material is provided as a cured product of any of the curable compositions disclosed herein. In some embodiments, the composite material can satisfy both of the following properties:

[0019] Moisture permeability (40℃, 92%RH) is 300g / m 2 Less than 24 hours; and

[0020] The haze is less than 10%.

[0021] According to the technology disclosed herein, a composite material having both low moisture permeability and high transparency can be realized.

[0022] In addition, according to the present specification, a method for producing a curable composition is provided. The method comprises mixing a layered compound (i.e., layered compound (A)) that has been organically treated with organic ions and the above-mentioned monomer raw material in the absence of a solvent. The above-mentioned method is suitable as a method for producing any curable composition disclosed herein.

[0023] It should be noted that appropriate combinations of the elements described in this specification may also be included in the scope of the invention claimed for patent protection through this application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a cross-sectional view schematically showing the structure of a laminate sheet including a composite material according to one embodiment.

[0025] Figure 2 It is a cross-sectional view schematically showing the structure of a laminate sheet including a composite material according to another embodiment.

[0026] Figure 3 This is a cross-sectional view schematically showing the structure of an optical layered body in which a composite material according to one embodiment is layered on an optical member. DETAILED DESCRIPTION

[0027] Hereinafter, a preferred embodiment of the present invention will be described. It should be noted that matters other than those specifically mentioned in this specification and required for the implementation of the present invention can be understood by those skilled in the art based on the teachings for the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented according to the contents disclosed in this specification and the technical common sense in the art. In addition, in the following drawings, the same reference numerals are sometimes used to illustrate components / parts that play the same role, and repeated descriptions are sometimes omitted or simplified. In addition, in order to clearly illustrate the present invention, the embodiments described in the drawings are schematically illustrated and do not necessarily accurately represent the size and scale of the adhesive sheet of the present invention of the actual product provided.

[0028] <Layered Compound (A)>

[0029] As the layered compound (A) in the technology disclosed herein, a layered compound (typically an inorganic layered compound) is used, which is obtained by organicizing a layered compound (typically an inorganic layered compound) with an organic ion. Examples of the above-mentioned layered compounds include: bentonite group, vermiculite, illite, kaolinite, halloysite, talc, mica, etc. Preferred layered silicate compounds, among which bentonite group is preferred. As the bentonite group, for example, montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, stevensite, etc. can be listed. As a layered compound, any one of a layered compound produced as a natural mineral, a layered compound obtained by purifying a natural mineral, and a synthetic layered compound can be used. From the viewpoint of quality stability, a layered compound obtained by purifying a natural mineral and a synthetic layered compound (such as a synthetic bentonite group) are advantageous.

[0030] The layered compound (A) may have a structure in which an organic ion is introduced into the above-mentioned layered compound (preferably a layered silicate compound). For example, the exchangeable inorganic ion (Na + Mg 2+ The structure obtained by reacting with organic cations (etc.)

[0031] Examples of the above-mentioned organic cations include organic cations (phosphonium ions) such as organic ammonium, imidazolium, pyridinium, and phosphonium. Examples of organic ammonium include tetraalkylammonium such as trioctylmethylammonium and dimethyldistearylammonium; examples include ammoniums having alkyl and aryl groups such as stearyldimethylbenzylammonium; examples include ammoniums containing polyoxyalkylene structures such as polyoxypropylenemethyldiethylammonium; and the like. Examples of imidazolium include methylstearylimidazolium, distearyllimidazolium, methylhexyllimidazolium, dihexyllimidazolium, methyloctyllimidazolium, dioctyllimidazolium, methyldodecyllimidazolium, didodecyllimidazolium, and the like. Examples of pyridinium include stearyl pyridinium, hexyl pyridinium, octyl pyridinium, and dodecyl pyridinium. Examples of phosphonium include dodecyl triphenyl phosphonium, methyl triphenyl phosphonium, lauryl trimethyl phosphonium, stearyl trimethyl phosphonium, distearyl dimethyl phosphonium, and distearyl diphenyl phosphonium. The counter anion of the organic cation used for ion exchange may be, for example, Cl - , B - Br - wait.

[0032] In some embodiments of the technology disclosed herein, the organic cation is preferably an organic ammonium. Preferred examples of the organic ammonium include: an alkyl group having a carbon number of 12 or more and 20 or less on the nitrogen atom (hereinafter, "carbon number of X or more and Y or less" is sometimes referred to as "C X-Y ”), C 4-11 Alkyl (e.g. C 6-10 Alkyl), C 1-3 An organic ammonium having a total of 4 groups in the group consisting of an alkyl group and a polyoxyalkylene group (for example, a polyoxypropylene group). As the alkyl group, a chain alkyl group is preferred, and a straight-chain alkyl group is more preferred, from the viewpoint of ion exchangeability.

[0033] In some embodiments, the organic ammonium may be a compound having 1 or more and 4 or less (preferably 1 or more and 3 or less, for example 2 or 3) C 4-11 an alkyl group and 0 or more and 3 or less (preferably 1 or more and 3 or less, for example 1 or 2) C 1-3 Here, C 1-3 The number of alkyl groups is 0, which means that there is no C 1-3 As a specific example of the above-mentioned organic ammonium, trioctylmethylammonium can be cited. This method is advantageous from the perspective of transparency and barrier properties of the cured product (composite material) formed by the curable composition. As a reason for this, it is believed that the above-mentioned organic ammonium has C 4-11The alkyl group has a large spacing between the layers constituting the layered compound, weakens the interaction between the layers, and imparts moderate hydrophobicity, so that the liquid phase containing the polar monomer (m1) easily enters the interlayers of the layered compound (A), and the dispersion ease of the layered compound (A) in the liquid phase is improved. From the viewpoint of affinity with the polar monomer (m1), the organic ammonium does not have C 12 The above long-chain alkyl groups are advantageous.

[0034] In other embodiments, the organic ammonium may have 1 or more and 3 or less (eg, 2 or 3) C 1-3 An organic ammonium having an alkyl group and 1 to 3 (e.g., 1 or 2) polyoxypropylene groups. This method is advantageous from the viewpoint of the ease of dispersion of the layered compound (A) in the curable composition, and further from the viewpoint of achieving a good dispersion state of the layered compound (A) in the cured product (composite material) formed by the curable composition. As a reason for this, it is believed that the organic ammonium has a polyoxypropylene group, so that the intervals between the layers constituting the layered compound are enlarged, the interlayer interaction of the layered compound is weakened, and moderate hydrophobicity is imparted, resulting in that the liquid phase containing the polar monomer (m1) easily enters the interlayer of the layered compound (A), and the ease of dispersion of the layered compound (A) in the liquid phase is improved. As a preferred example of the above-mentioned organic ammonium, for example, polyoxypropylene trialkylammonium represented by the following formula (1) can be cited:

[0035] [R 1 R 2 R 3 N(CH2CH(CH3)O) n -H] + (1);

[0036] R in the above formula (1) 1 , R 2 , R 3 Each is independently a methyl group or an ethyl group, and n is 2 to 50 (preferably 15 to 35). In some embodiments, the lower limit of the range of n in the above formula (1) may be, for example, any one of 5, 10, 15 and 20, and the upper limit of the range of n may be, for example, any one of 45, 40, 35 and 30. As a preferred example of the compound represented by formula (1), polyoxypropylene methyl diethyl ammonium can be cited.

[0037] In some embodiments of the curable composition or its cured product (composite material) disclosed herein, the layered compound (A) is preferably dispersed in the liquid phase or matrix phase in the form of plate-like particles having a thickness of about 0.5 nm to about 20 nm (preferably about 0.8 nm to about 10 nm, more preferably about 0.8 nm to about 5 nm, for example about 1 nm) and an average length of about 30 nm to about 3000 nm (preferably about 40 nm to about 1000 nm, more preferably about 50 nm to about 500 nm, for example about 100 nm to about 200 nm). Most of the plate-like particles (for example, 60% by weight or more, preferably 80% by weight or more, more preferably 95% by weight or more) are preferably a single-layer structure containing only one layer of the layer possessed by the layered compound (A) before dispersion. It should be noted that the average length of the plate-like particles refers to the arithmetic mean of the length of the longer side (the length of the long side) of the plate-like particles in the vertical and horizontal directions. The average aspect ratio of the plate-like particles can be, for example, 10 or more and 2000 or less, preferably 20 or more and 1000 or less, more preferably 50 or more and 500 or less (e.g., 100 or more and 200 or less). The average aspect ratio refers to the arithmetic mean of the ratio (aspect ratio) of the length of the long side of each plate-like particle to the thickness. The average length and average aspect ratio of the plate-like particles can be obtained, for example, by analyzing a transmission electron microscope (TEM) image.

[0038] The layered compound that has been organized using organic ions is prepared by converting the exchangeable inorganic ions (Na + Mg 2+ The organic layered compound is obtained by ion exchange with organic cations. Examples of commercially available organic layered compounds include: SUMECTON (trade name) STN, SAN, SAN-P, SSN, SPN-E, SEN manufactured by Kunimine Industries; Kunivis (trade name) 110, 127 manufactured by the same company; and Minstite (trade name) WO manufactured by the same company.

[0039] The curable composition disclosed herein can contain the layered compound (A) in the cured product of the curable composition with a content of about 1% by weight or more. That is, the above-mentioned curable composition can contain the above-mentioned layered compound (A) with a weight of the layered compound (A) in the overall weight of its cured product reaching about 1% by weight or more. In a solvent-free curable composition, the content of the layered compound (A) in the curable composition is roughly consistent with the content of the layered compound (A) in the cured product. In some ways, the content of the layered compound (A) in the above-mentioned cured product can be, for example, 3% by weight or more, and from the viewpoint of obtaining a higher use effect, it is appropriate to be 5.0% by weight or more, and it is advantageous to be 7.5% by weight or more, preferably 10% by weight or more, 13.5% by weight or more, 15% by weight or more, 16.5% by weight or more, and 18% by weight or more. The content of the layered compound (A) in the above-mentioned cured product can be, for example, 50% by weight or less. From the viewpoint of dispersibility, properties of the cured product (e.g., adhesive properties, optical properties), etc., it is advantageous to have a content of 45% by weight or less, preferably 42% by weight or less, more preferably 38% by weight or less, and can be 35% by weight or less, 32% by weight or less, 28% by weight or less, 25% by weight or less, or 20% by weight or less.

[0040] <Monomer Raw Materials>

[0041] The monomer raw material in the technology disclosed herein may include only one monomer or a mixture including two or more monomers. From the viewpoint of easily forming a cured product by the curable composition disclosed herein, it is preferred to have a monomer having a polymerizable functional group that can be polymerized by active energy rays (e.g., ultraviolet rays, visible light, infrared rays, such as α rays, β rays, γ rays, electron rays, neutron rays, X-rays, etc.) or heat, for example, a monomer preferably having an ethylenically unsaturated group. As examples of the above-mentioned ethylenically unsaturated groups, (methyl) acryloyl, vinyl, (methyl) allyl, etc. can be cited. As a monomer constituting the monomer raw material, from the viewpoints of the flexibility of the cured product, it is preferred to use a monomer (monofunctional monomer) having one polymerizable functional group in one molecule.

[0042] Here, in this specification, "(meth)acryloyl" collectively means acryloyl and methacryloyl. Similarly, in this specification, "(meth)acrylate" collectively means acrylate and methacrylate, "(meth)acrylic acid" collectively means acrylic acid and methacrylic acid, and "meth(allyl)" collectively means allyl and methallyl. In addition, in this specification, a monomer having at least one (meth)acryloyl group in one molecule is sometimes referred to as an "acrylic monomer". The concept of the above-mentioned acrylic monomer may include both monomers having an acryloyl group (acrylic monomer) and monomers having a methacryloyl group (methacrylic monomer). From the viewpoints of weather resistance, optical properties, adhesive properties, etc., the technology disclosed herein may preferably be implemented in a manner in which the proportion of acrylic monomers in the monomer raw material is greater than 50% by weight (preferably greater than 70% by weight, for example greater than 90% by weight).

[0043] (Polar monomer (m1))

[0044] The monomer raw material in the technology disclosed herein contains a polar monomer (m1). By using a polar monomer (m1), the above-mentioned layered compound (A) can be more easily dispersed in a liquid phase containing the polar monomer (m1). As a reason for this, without making a particularly restrictive explanation, it is believed that the polar monomer (m1) easily enters the interlayer of the layered compound (A), which helps to promote interlayer separation (the formation of plate-like particles). As a polar monomer (m1), a monomer having a polar group is used, and examples of the polar group include: amide group, imide group, cyano group, isocyanate group, amino group, nitrogen atom-containing ring, hydroxyl group, carboxyl group, sulfonic acid group, phosphoric acid group, etc. The polar monomer (m1) contained in the monomer raw material may be only one type, or may be two or more types.

[0045] Examples of amide group-containing monomers include (meth)acrylamide; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, N,N-di(tert-butyl) (meth)acrylamide and the like N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide and the like N-alkyl (meth)acrylamide; N-vinyl carboxylic acid amides such as N-vinylacetamide; amide group-containing monomers having a hydroxyl group, such as N-(2-hydroxyethyl) (meth)acrylamide; N-hydroxyalkyl(meth)acrylamide, such as acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(2-hydroxybutyl)(meth)acrylamide, N-(3-hydroxybutyl)(meth)acrylamide, and N-(4-hydroxybutyl)(meth)acrylamide; amide group-containing monomers having an alkoxy group, such as N-methoxymethyl(meth)acrylamide, N-methoxyethyl(meth)acrylamide, and N-butoxymethyl(meth)acrylamide; in addition, N,N-dimethylaminopropyl(meth)acrylamide, N-(meth)acryloylmorpholine, and N-vinyl cyclic amides.

[0046] Examples of monomers containing an imide group include: monomers having a succinimide skeleton, such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyhexamethylenesuccinimide; monomers having a maleimide skeleton, such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; monomers having an itaconimide skeleton, such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide; and the like.

[0047] Examples of the cyano group-containing monomer include acrylonitrile and methacrylonitrile, and examples of the isocyanate group-containing monomer include 2-isocyanatoethyl (meth)acrylate.

[0048] Examples of amino group-containing monomers include N,N-dimethylaminomethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminobutyl (meth)acrylate, N,N-dimethylaminohexyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dipropylaminoethyl (meth)acrylate, N,N-dibutylaminoethyl (meth)acrylate, and N,N-dimethylaminobutyl (meth)acrylate. N,N-dialkylaminoalkyl (meth)acrylates such as N-methyl-N-ethylaminoethyl (meth)acrylate, N-methyl-N-butylaminoethyl (meth)acrylate, and N,N-dipropylaminopropyl (meth)acrylate; N-alkylaminoalkyl (meth)acrylates such as N-methylaminoethyl (meth)acrylate, N-ethylaminoethyl (meth)acrylate, N-isopropylaminoethyl (meth)acrylate, N-tert-butylaminoethyl (meth)acrylate, and N-butylaminoethyl (meth)acrylate.

[0049] Examples of monomers having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyl oxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3- Oxazine-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinyliso azole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc.

[0050] Examples of monomers having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.

[0051] Examples of the monomer having a carboxyl group include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0052] Examples of monomers containing a sulfonic acid group or a phosphoric acid group include styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, (meth)acryloyloxynaphthalenesulfonic acid, and 2-hydroxyethylacryloyl phosphate.

[0053] The content of the polar monomer (m1) in the monomer raw material can be, for example, 0.5% by weight or more. From the perspective of easily exerting the effect brought about by the use of the polar monomer (m1), it is advantageous to be 1.0% by weight or more, preferably 2.0% by weight or more, more preferably 3.0% by weight or more or 4.0% by weight or more, 5.0% by weight or more (for example, greater than 5.0% by weight), 6.0% by weight or more, 7.0% by weight or more, 8.0% by weight or more, 9.0% by weight or more, 10% by weight or more, 15% by weight or more, or 18% by weight or more. The content of the polar monomer (m1) in the monomer raw material can be 100% by weight. From the perspective of the softness of the cured product (composite material), it is appropriate to be 70% by weight or less, preferably 50% by weight or less, 35% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, or 12% by weight or less.

[0054] In some embodiments, as the polar monomer (m1), a monomer without a cyclic structure, i.e., a non-cyclic polar monomer, can be preferably used. As a non-cyclic polar monomer, a polar monomer without a cyclic structure among the polar monomers (m1) exemplified above can be used. For example, preferably, more than 50% by weight, more than 70% by weight, or more than 90% by weight of the polar monomer (m1) contained in the monomer raw material is a non-cyclic monomer. 100% by weight of the polar monomer (m1) can be a non-cyclic monomer.

[0055] (nitrogen-containing monomer (m1 N ))

[0056] In some embodiments of the technology disclosed herein, the above-mentioned monomer raw material preferably includes a nitrogen atom-containing monomer (m1 N ) as the polar monomer (m1). N ), a monomer containing a nitrogen atom among the polar monomers (m1) can be cited. For example, a monomer belonging to at least any one of an amide group-containing monomer, an imide group-containing monomer, a cyano group-containing monomer, an isocyanate group-containing monomer, an amino group-containing monomer, and a nitrogen atom ring-containing monomer can be used as the monomer (m1). N ). Monomer (m1 N ) can be used alone or in combination of two or more.

[0057] The monomer in the monomer raw material (m1 N ) content can be, for example, 0.5 wt % or more, from the monomer (m1 N ) is advantageous from the viewpoint of the effect of using the monomer raw material, and is preferably greater than 2.0 wt %, more preferably greater than 3.0 wt % (e.g. greater than 4.0 wt %), and may be greater than 5.0 wt %, greater than 6.0 wt %, greater than 7.0 wt %, greater than 8.0 wt %, or greater than 9.0 wt % (e.g. greater than 9.0 wt %). From the viewpoint of the softness of the cured product (composite material), the monomer (m1 N ) content is appropriately 70 wt % or less, preferably 50 wt % or less, can be 35 wt % or less, can be 25 wt % or less, can be 20 wt % or less, can be 15 wt % or less, can be 10 wt % or less.

[0058] The monomer (m1) in the polar monomer (m1) N ) content can be, for example, 10 wt % or more, from the monomer (m1 N ) is advantageously 25 wt % or more, preferably 50 wt % or more, and may be 75 wt % or more, or 90 wt % or more. N ) may be 100 wt %. That is, as the polar monomer (m1), only one or two or more monomers (m1) may be used. N ). In some embodiments, the monomer (m1) in the polar monomer (m1) N ) may be present in an amount of 60 wt % or less, 30 wt % or less, 15 wt % or less, or 5 wt % or less.

[0059] The monomer raw material contains a nitrogen-containing monomer (m1 N ), except for the monomer (m1 N ) may contain, for example, less than 10% by weight of the polar monomer (m1) in order to better exert the effect of the monomer (m1) N ) is preferably less than 5.0 wt %, more preferably less than 3.0 wt %, may be less than 1.0 wt %, may be less than 0.5 wt %, or may be less than 0.1 wt %. It is also possible not to use the monomer (m1 N ) other than the polar monomer (m1). That is, the monomer raw material except the monomer (m1 N ) may be contained in an amount of 0% by weight.

[0060] In some embodiments, as a monomer (m1 N), an amide group-containing monomer can be preferably used. Preferred examples of amide group-containing monomers include the above-mentioned various N,N-dialkyl (meth) acrylamides, non-cyclic amides such as N-alkyl (meth) acrylamides; cyclic amides such as N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam, etc., but are not limited to these substances. The amide group-containing monomer can be used alone or in combination of two or more.

[0061] The content of the amide-containing monomer in the monomer raw material can be, for example, 0.5% by weight or more. From the viewpoint of easily exerting the effect brought about by the use of the amide-containing monomer, it is advantageous to be greater than 1.0% by weight, preferably greater than 2.0% by weight, more preferably greater than 3.0% by weight (for example, greater than 4.0% by weight), greater than 5.0% by weight, greater than 6.0% by weight, greater than 7.0% by weight, greater than 8.0% by weight, or greater than 9.0% by weight (for example, greater than 9.0% by weight). From the viewpoint of the softness of the cured product (composite material), it is appropriate that the content of the amide-containing monomer in the monomer raw material is less than 70% by weight, preferably less than 50% by weight, less than 35% by weight, less than 25% by weight, less than 20% by weight, less than 15% by weight, or less than 10% by weight.

[0062] The content of the amide group-containing monomer in the polar monomer (m1) may be, for example, 10% by weight or more, preferably 25% by weight or more, more preferably 50% by weight or more, 75% by weight or more, 90% by weight or more, or 100% by weight. In addition, in some embodiments, the content of the amide group-containing monomer in the polar monomer (m1) may be 60% by weight or less, 30% by weight or less, 15% by weight or less, or 5% by weight or less.

[0063] Monomer (m1 N ) may contain an amide group-containing monomer in an amount of, for example, 10 wt % or more, preferably 25 wt % or more, more preferably 50 wt % or more, 75 wt % or more, 90 wt % or more, or 100 wt %. In some embodiments, the monomer (m1 N ) may contain an amide group-containing monomer in an amount of 60 wt % or less, 30 wt % or less, 15 wt % or less, or 5 wt % or less.

[0064] In some embodiments, as a monomer (m1 N ), a monomer having no cyclic structure, i.e., an acyclic monomer, can be preferably used. The acyclic monomer (m1 N ) in its molecular structure with the monomer (m1 N) tends to easily enter the interlayers of the layered compound (A), thereby effectively contributing to the facilitation of the dispersion of the layered compound. N Preferred examples of the monomer (m1) include non-cyclic amides (chain amides) such as N,N-dialkyl (meth) acrylamide and N-alkyl (meth) acrylamide. In the non-cyclic amide, it is advantageous for the number of carbon atoms of each alkyl group bonded to the nitrogen atom to be 1 to 4, preferably 1 to 3, and more preferably 1 or 2 (for example, 1). When the number of carbon atoms of the above alkyl group is 3 or more (for example, 3 or 4), it is preferably a straight-chain alkyl group. Monomer (m1 N ) may contain, for example, 10 wt % or more, preferably 25 wt % or more, more preferably 50 wt % or more, may be 75 wt % or more, may be 90 wt % or more, may be 100 wt %.

[0065] (monomer(m2))

[0066] In addition to the polar monomer (m1), the above-mentioned monomer raw material may further contain a (meth)acrylic acid chain alkyl ester (m2) having a chain alkyl group with 4 to 20 carbon atoms at the ester end (i.e., monomer (m2)). The chain alkyl group at the ester end may be a straight chain or a branched chain. Monomer (m2) may contribute to the adjustment of the coating properties of the curable composition, the adjustment of the viscoelasticity of the cured product (composite material) formed by the curable composition, the suppression of the coloring of the cured product, etc. Monomer (m2) may be used alone or in combination of two or more.

[0067] As the monomer (m2), there can be mentioned alkyl (meth)acrylates represented by the following formula (2):

[0068] CH2=CR 1 (C=O)-OR 2 (2);

[0069] Among them, R in the above formula (2) 1 is a hydrogen atom or a methyl group, R 2 C 4-20Specific examples of the monomer (m2) represented by the above formula (2) include: n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, etc. In some embodiments, R can be preferably used. 2 C 6-20 (For example, C 8-20 ) is a monomer (m2) having a chain alkyl group.

[0070] The content of monomer (m2) in the monomer raw material can be set within the range of not more than 100 weight % with the total content of polar monomer (m1). The content of monomer (m2) in the monomer raw material can be, for example, 5.0 weight % or more. From the perspective of easily exerting the use effect of monomer (m2), it is appropriate to be 10 weight % or more, and it is advantageous to be 30 weight % or more, and it can be 45 weight % or more or 50 weight % or more. In some embodiments, the content of monomer (m2) in the monomer raw material is preferably 55 weight % or more, more preferably 60 weight % or more, can be 70 weight % or more, can be 80 weight % or more, and can be 90 weight % or more. In addition, the content of the monomer (m2) in the monomer raw material can be, for example, 99.5% by weight or less. From the perspective of easily exerting the use effect of the polar monomer (m1), it is advantageous to be 99.0% by weight or less, preferably 98.0% by weight or less, preferably 97.0% by weight or less or 96.0% by weight or less, and can be 95% by weight or less (for example, less than 95% by weight), 94% by weight or less, 93% by weight or less, 92% by weight or less, or 91% by weight or less. In some embodiments, the content of the monomer (m2) in the monomer raw material can be 90% by weight or less, 85% by weight or less, 80% by weight or less, or 75% by weight or less.

[0071] (monomer(m2 L ))

[0072] In some aspects of the technology disclosed herein, the monomer raw material preferably contains a (meth)acrylic acid chain alkyl ester (m2) having a chain alkyl group with 13 to 20 carbon atoms (more preferably 15 to 20, for example 16 to 20) at the ester end. L )(i.e., monomer (m2 L )) as the above monomer (m2). L ), R in the above formula (2) can be preferably used 2 C 13-20 (More preferably C 15-20 For example, C 16-20 ) chain alkyl (meth) acrylate. Monomer (m2 L ) can contribute to the reduction of the moisture permeability of the cured product due to the hydrophobicity of the long-chain alkyl group having 13 or more carbon atoms (preferably 15 or more, for example 16 or more). In addition, by having the long-chain alkyl group, it can also contribute to the improvement of compatibility with low-polarity softeners (for example, low-polarity liquid rubbers such as liquid polybutadiene), thereby contributing to the improvement of transparency. Monomer (m2 L ) can be used alone or in combination of two or more.

[0073] Monomers in the monomer raw material (m2 L The content of ) can be set within the range of not more than 100 wt % of the total content of other monomers, for example, it can be 5.0 wt % or more, from the monomer (m2 L ) from the perspective of the use effect, 10 wt % or more is advantageous, preferably 30 wt % or more, more preferably 45 wt % or more, can be 50 wt % or more, can be 55 wt % or more, can be 70 wt % or more, can be 80 wt % or more, can be 90 wt % or more. In addition, the monomer (m2 L ) content can be, for example, 99.5 wt % or less. From the viewpoint of easily exerting the effect of using the polar monomer (m1), it is advantageous to have a content of 99.0 wt % or less, preferably 98.0 wt % or less, more preferably 97.0 wt % or less or 96.0 wt % or less, and can be 95 wt % or less (for example, less than 95 wt %), and can be 94 wt % or less, 93 wt % or less, 92 wt % or less, 91 wt % or less, 90 wt % or less, 85 wt % or less, 80 wt % or less or 75 wt % or less.

[0074] Monomer (m2) in monomer (m2 L ) content can be, for example, 1.0 wt % or more, from the monomer (m2 L), 5.0 wt % or more is appropriate, preferably 15 wt % or more, more preferably 30 wt % or more, 50 wt % or more, 70 wt % or more, 90 wt % or more, or 100 wt %. In some embodiments, the monomer (m2) in the monomer (m2) L ) may be present in an amount of 80 wt % or less, 60 wt % or less, 40 wt % or less, 20 wt % or less, or 10 wt % or less.

[0075] (Other monomers)

[0076] The monomer raw material in the technology disclosed herein may contain a monomer (hereinafter also referred to as "other monomer") which is copolymerizable with the polar monomer (m1) and does not belong to either the polar monomer (m1) or the monomer (m2) as needed. The above-mentioned other monomers may be used alone or in combination of two or more.

[0077] Specific examples of the other monomers include:

[0078] A (meth)acrylic acid chain alkyl ester having a chain alkyl group with 1 to 3 carbon atoms at the ester terminal, specifically methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate; a (meth)acrylic acid chain alkyl ester having a chain alkyl group with 21 or more carbon atoms (e.g., C 21-30 (meth)acrylates having an alicyclic hydrocarbon group such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrodicyclopentadienyl (meth)acrylate, and adamantyl (meth)acrylate; (meth)acrylates having an aromatic ring such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene, α-methylstyrene, and vinyltoluene; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; 2-methoxyethyl (meth)acrylate and 3-methoxypropyl (meth)acrylate , alkoxy-containing monomers such as 2-ethoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; alkoxysilyl-containing monomers such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; epoxy-containing monomers such as glycidyl (meth)acrylate, methylglycidyl (meth)acrylate, and allyl glycidyl ether; olefins such as ethylene, propylene, butadiene, isoprene, and isobutylene; chlorine-containing monomers such as vinyl chloride and vinylidene chloride; etc., but not limited to these substances.

[0079] The content of the above-mentioned other monomers in the monomer raw material can be set within a range where the total content of the other monomers is not more than 100% by weight. From the viewpoint of easily obtaining a balance of characteristics in a cured product, in some embodiments, the content of the above-mentioned other monomers in the monomer raw material is appropriately 40% by weight or less, preferably 25% by weight or less, more preferably 20% by weight or less, 15% by weight or less, 10% by weight or less, 5.0% by weight or less, 3.0% by weight or less, 1.0% by weight or less or 0.5% by weight or less. Other monomers may also not be used.

[0080] (Calculate Tg)

[0081] In the technology disclosed herein, for the polymer corresponding to the composition of the monomer raw material, the glass transition temperature (hereinafter also referred to as "calculated Tg") calculated based on the composition of the monomer raw material is not particularly limited, and can be, for example, in the range of about -80°C or more and about 60°C or less. The above-mentioned calculated Tg can be, for example, 40°C or less, 20°C or less, or 10°C or less. In some embodiments, from the viewpoints of the flexibility and adhesiveness of the cured product, it is appropriate that the above-mentioned calculated Tg is 0°C or less or less than 0°C, and can be -3°C or less, -5°C or less, -10°C or less, -20°C or less, -30°C or less, -40°C or less, -50°C or less, or -60°C or less. In addition, from the viewpoints of the gas barrier properties and shape retention of the cured product, in some embodiments, the above-mentioned calculated Tg is advantageously -70°C or more, and can be -65°C or more, -45°C or more, -35°C or more, -25°C or more, -20°C or more, or -15°C or more.

[0082] Here, the calculated Tg of the monomer raw material refers to the Tg obtained by the Fox equation based on the composition of the above-mentioned monomer raw material. The Fox equation is shown below and is a relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing the monomers constituting the copolymer.

[0083] 1 / Tg=Σ(Wi / Tgi)

[0084] It should be noted that in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).

[0085] As the glass transition temperature of the homopolymer used in the calculation of Tg, the value described in the known document is used. For example, for the monomers listed below, as the glass transition temperature of the homopolymer of the monomer, the following value is used.

[0086] n-Butyl acrylate-55℃

[0087] 2-Ethylhexyl acrylate -70℃

[0088] Isostearyl acrylate-18℃

[0089] N,N-Dimethylacrylamide 119℃

[0090] N-vinyl pyrrolidone 54℃

[0091] Acrylic acid 106℃

[0092] Regarding the glass transition temperature of homopolymers of monomers other than those exemplified above, the values ​​recorded in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) are used. For monomers for which multiple values ​​are recorded in the document, the highest value is adopted. Regarding monomers for which the glass transition temperature of homopolymers is not recorded in the above-mentioned polymer handbook, the values ​​obtained by the measurement method described in Japanese Patent Application Publication No. 2007-51271 are used. For monomers for which the nominal value of the glass transition temperature of homopolymers is provided by manufacturers, the nominal value can be adopted.

[0093] <Softener>

[0094] The curable composition disclosed herein may contain a softener. The softener contained in the curable composition is typically a constituent component of the liquid phase, and can contribute to the adjustment of the fluidity of the curable composition and the adjustment of the properties (e.g., flexibility, optical properties) of the cured product formed by the curable composition. In some embodiments, from the perspective of the ease of preparation of the curable composition, a softener that is liquid at least at 30°C may be preferably used. A softener that is liquid at 25°C is more preferred. Here, being liquid at a specified temperature means that the viscosity at that temperature is less than 2000Pa·s, preferably less than 1000Pa·s, and more preferably less than 500Pa·s. The lower limit of the viscosity of the softener at the above temperature is not particularly limited, for example, it may be greater than 0.005Pa·s or greater than 0.01Pa·s.

[0095] Examples of materials that can be used as softeners in the technology disclosed herein include liquid rubber softeners such as liquid polybutadiene, liquid polyisoprene, liquid polyisobutylene, and liquid polybutene; examples of olefin softeners include ethylene-butene copolymers, ethylene-propylene-butene copolymers, propylene-butene copolymers, ethylene-butene-non-conjugated diene copolymers, and ethylene-propylene-butene-non-conjugated diene copolymers; examples of paraffin processing oils, cycloparaffin processing oils, aromatic processing oils, and the like. Oil softeners such as industrial oils; examples include polyoxyalkylene glycol softeners such as polyoxypropylene glycol and polyoxytetramethylene glycol; examples include oligomer softeners such as urethane oligomers and acrylic oligomers; examples include liquid tackifying resins such as liquid rosin esters (such as hydrogenated rosin methyl ester), liquid terpene phenol resins, and liquid xylene resins; examples include plasticizers such as aromatic carboxylic acid ester plasticizers, aliphatic carboxylic acid ester plasticizers, and polyester plasticizers; etc., but are not limited to these substances.

[0096] The molecular weight of the softener can be, for example, 50,000 or less, 30,000 or less is appropriate, 15,000 or less is advantageous, preferably 10,000 or less or less than 10,000, 7000 or less, 5000 or less, 3500 or less, 3000 or less, 2500 or less, 2000 or less, or 1800 or less. From the viewpoint of the ease of preparation of the curable composition containing the softener and the improvement of the compatibility (and transparency) in the cured product, it is advantageous that the molecular weight of the softener is not too large. The lower limit of the molecular weight of the softener is not particularly limited, for example, it can be more than 250, more than 300 or more than 350. From the viewpoint of the characteristic stability of the cured product, in some embodiments, the molecular weight of the softener is preferably more than 500, more preferably more than 800, more than 1000, or more than 1200.

[0097] As the molecular weight of the softening agent, about the softening agent as a polymer of non-polymer or low degree of polymerization (e.g., about 2-mer to about 5-mer), the molecular weight calculated based on the chemical structure or the measured value using matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) can be used. For the softening agent as a polymer with a higher degree of polymerization, the number average molecular weight (Mn) based on the GPC performed under appropriate conditions can be used. In the case of providing the nominal value of the molecular weight by the manufacturer, the nominal value can be adopted.

[0098] The amount of the softener used can be, for example, 1 part by weight or more or 5 parts by weight or more relative to 100 parts by weight of the monomer raw material. From the viewpoint of obtaining a higher softening effect (plasticizing effect), in some embodiments, the amount of the softener used is appropriately 10 parts by weight or more relative to 100 parts by weight of the monomer raw material, and is advantageously 15 parts by weight or more, preferably 30 parts by weight or more (e.g., 32 parts by weight or more), can be 40 parts by weight or more, can be 50 parts by weight or more, can be 60 parts by weight or more, can be 70 parts by weight or more, can be 80 parts by weight or more. In addition, the amount of the softener used can be, for example, 300 parts by weight or less relative to 100 parts by weight of the monomer raw material. From the viewpoint of easily obtaining moderate cohesion in the cured product and the viewpoint of the characteristic stability of the cured product, it is advantageous to use 250 parts by weight or less, and is preferably 200 parts by weight or less, and can be 150 parts by weight or less, can be 120 parts by weight or less, can be 100 parts by weight or less, can be 75 parts by weight or less, 55 parts by weight or less, 35 parts by weight or less, 25 parts by weight or less, or 20 parts by weight or less.

[0099] <Curable Composition>

[0100] The curable composition disclosed herein is preferably substantially free of organic solvents, and more preferably substantially free of any one of organic solvents and aqueous solvents. That is, the above-mentioned curable composition is preferably free of organic solvents, and more preferably free of solvents. From the perspective of environmental hygiene of the curable composition and its cured product, a curable composition free of organic solvents is also preferred. The solvent-free curable composition does not require drying (removal of solvent) in the process of forming its cured product from the curable composition, so it is advantageous from the perspective of productivity and energy efficiency. For the same reason, the liquid phase of the curable composition disclosed herein is preferably substantially free of organic solvents, and more preferably substantially free of any one of organic solvents and aqueous solvents. That is, the above-mentioned liquid phase is preferably free of organic solvents, and more preferably free of solvents. Here, "substantially free of" means that the content in the object (curable composition or liquid phase) is 3% by weight or less (preferably 1% by weight or less, more preferably 0.5% by weight or less, and further preferably 0.1% by weight or less), including the case where the above-mentioned content is 0% by weight. Therefore, for example, the curable composition is solvent-free, which means that the weight of all solvents contained in the curable composition (the total amount of organic solvents and aqueous solvents) is 0% by weight or more and 3% by weight or less (preferably 1% by weight or less, more preferably 0.5% by weight or less, and further preferably 0.1% by weight or less) in the total weight (100% by weight) of the curable composition. It should be noted that the solvent refers to a volatile component that should be removed in the process of forming a cured product from the curable composition, that is, a volatile component that is not intended to become a constituent component of the cured product finally formed.

[0101] (Content of layered compound (A))

[0102] In the curable composition disclosed herein, the content of the layered compound (A) can be, for example, 1 part by weight or more, 5 parts by weight or more is appropriate, and 8 parts by weight or more is advantageous from the viewpoint of obtaining a higher use effect, preferably 10 parts by weight or more, more preferably 12 parts by weight or more, 15 parts by weight or more, 18 parts by weight or more, or 20 parts by weight or more. In some embodiments, the content of the layered compound (A) can be 25 parts by weight or more, 30 parts by weight or more, greater than 30 parts by weight (e.g., 32 parts by weight or more), or 35 parts by weight or more, relative to 100 parts by weight of the monomer raw material. In addition, the content of the layered compound (A) relative to 100 parts by weight of the monomer raw material can be, for example, 100 parts by weight or less. From the viewpoint of ease of dispersion, properties of the cured product (e.g., adhesive properties, optical properties), etc., it is appropriate to be 70 parts by weight or less, preferably 60 parts by weight or less, more preferably 50 parts by weight or less, and can be 45 parts by weight or less, can be 40 parts by weight or less, can be 35 parts by weight or less, can be 30 parts by weight or less, or can be 25 parts by weight or less.

[0103] In the case where the curable composition includes a softener, the content of the layered compound (A) may be, for example, 1 part by weight or more, and 5 parts by weight or more is appropriate, relative to 100 parts by weight of the total amount of the monomer raw material and the softener. From the viewpoint of obtaining a higher use effect, 8 parts by weight or more is advantageous, preferably 10 parts by weight or more, more preferably 12 parts by weight or more, 15 parts by weight or more, 18 parts by weight or more, or 20 parts by weight or more. In addition, relative to 100 parts by weight of the total amount of the monomer raw material and the softener, the content of the layered compound (A) may be, for example, 70 parts by weight or less, and from the viewpoint of ease of dispersion, properties of the cured product (e.g., adhesive properties, optical properties), 50 parts by weight or less is appropriate, preferably 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less.

[0104] (Polymerization initiator)

[0105] The curable composition disclosed herein is preferably configured to be cured by light (preferably ultraviolet rays) or heat to form a cured product. That is, the above-mentioned curable composition is preferably photocurable and / or thermosetting. In some preferred embodiments, the above-mentioned curing is accompanied by a polymerization reaction of a monomer raw material. In the curable composition of this mode, a known or commonly used photopolymerization initiator or a thermal polymerization initiator may be contained as required. A polymerization initiator may be used alone or in combination of two or more.

[0106] There are no particular restrictions on the photopolymerization initiator, and for example, ketal-type photopolymerization initiators, acetophenone-type photopolymerization initiators, benzoin ether-type photopolymerization initiators, acylphosphine oxide-type photopolymerization initiators, α-ketol-type photopolymerization initiators, aromatic sulfonyl chloride-type photopolymerization initiators, photoactive oxime-type photopolymerization initiators, benzoin-type photopolymerization initiators, benzyl-type photopolymerization initiators, benzophenone-type photopolymerization initiators, thioxanthone-type photopolymerization initiators, etc. can be used.

[0107] Specific examples of the ketal-based photopolymerization initiator include 2,2-dimethoxy-1,2-diphenylethane-1-one (for example, trade name "Omnirad 651" manufactured by IGM Resins Co., Ltd.) and the like.

[0108] Specific examples of acetophenone-based photopolymerization initiators include: 1-hydroxycyclohexyl phenyl ketone (for example, the trade name "Omnirad 184" manufactured by IGM Resins), 4-phenoxydichloroacetophenone, 4-tert-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropanone (for example, the trade name "Omnirad 2959" manufactured by IGM Resins), 2-hydroxy-2-methyl-1-phenyl-propane-1-one (for example, the trade name "Omnirad 1173" manufactured by IGM Resins), methoxyacetophenone, etc.

[0109] Specific examples of the benzoin ether-based photopolymerization initiator include benzoin ethers such as benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, and benzoin isobutyl ether, and substituted benzoin ethers such as anisole methyl ether.

[0110] Specific examples of the acylphosphine oxide-based photopolymerization initiators include: bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (for example, the trade name "Omnirad819" manufactured by IGM Resins), bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (for example, the trade name "Omnirad TPO" manufactured by IGM Resins), bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, etc.

[0111] Specific examples of α-ketol photopolymerization initiators include: 2-methyl-2-hydroxypropiophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropanone, etc. Specific examples of aromatic sulfonyl chloride photopolymerization initiators include 2-naphthalenesulfonyl chloride, etc. Specific examples of photoactive oxime photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl)-oxime, etc. Specific examples of benzoin photopolymerization initiators include benzoin, etc. Specific examples of benzyl photopolymerization initiators include benzyl, etc.

[0112] Specific examples of the benzophenone-based photopolymerization initiator include benzophenone, benzoylbenzoic acid, 3,3′-dimethyl-4-methoxybenzophenone, poly(vinyl benzophenone), and α-hydroxycyclohexyl phenyl ketone.

[0113] Specific examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.

[0114] The thermal polymerization initiator is not particularly limited, and for example, an azo polymerization initiator, a persulfate, a peroxide initiator, a substituted ethane initiator, etc. can be used. More specifically, examples include: azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate; examples include: persulfates such as potassium persulfate and ammonium persulfate; peroxide initiators such as benzoyl peroxide, tert-butyl hydroperoxide, and hydrogen peroxide; examples include substituted ethane initiators such as phenyl-substituted ethane; and the like, but are not limited to these substances.

[0115] The amount of such a thermal polymerization initiator or photopolymerization initiator used may be a normal amount according to the polymerization method, polymerization mode, etc., and is not particularly limited. For example, about 0.001 to about 5 parts by weight (typically about 0.01 to about 2 parts by weight, for example, about 0.01 to about 1 part by weight, or about 0.05 to about 0.5 parts by weight) of the polymerization initiator may be used relative to 100 parts by weight of the monomer raw material.

[0116] (Crosslinking agent)

[0117] The curable composition disclosed herein may contain a crosslinking agent as needed in order to adjust the cohesive force of the cured product. Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, aziridine crosslinking agents, The crosslinking agent is a crosslinking agent known in the adhesive field such as oxazoline crosslinking agents and metal chelate crosslinking agents. As other examples of crosslinking agents, monomers having more than two polymerizable functional groups (preferably ethylenically unsaturated groups) in one molecule, i.e., multifunctional monomers, can be cited. The crosslinking agent can be used alone or in combination of two or more. As an example of a preferred crosslinking agent, multifunctional monomers in photocurable compositions and isocyanate crosslinking agents in thermosetting compositions can be cited, but are not limited to these substances.

[0118] Examples of the polyfunctional monomer include ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, bisphenoxyethanol fluorene di(meth)acrylate, and bisphenol A di(meth)acrylate. In some embodiments, a trifunctional or higher polyfunctional monomer (ie, a monomer having three or more polymerizable functional groups in one molecule) may be preferably used. The polyfunctional monomer may be used alone or in combination of two or more.

[0119] The usage amount of the multifunctional monomer is not particularly limited, and can be appropriately set in a manner to achieve the purpose of use of the multifunctional monomer. Relative to 100 parts by weight of the monomer raw material, the usage amount of the multifunctional monomer can be, for example, less than 10 parts by weight, or less than 5.0 parts by weight. In some ways, from the viewpoints of the softness of the cured product, relative to 100 parts by weight of the monomer raw material, the usage amount of the multifunctional monomer is preferably less than 3.0 parts by weight, more preferably less than 1.5 parts by weight, less than 1.0 parts by weight, less than 0.5 parts by weight, or less than 0.3 parts by weight. The lower limit of the usage amount of the multifunctional monomer is not particularly limited. In some ways, from the viewpoint of appropriately exerting its use effect, relative to 100 parts by weight of the monomer raw material, the usage amount of the multifunctional monomer can be, for example, more than 0.001 parts by weight, more than 0.005 parts by weight, more than 0.01 parts by weight, or more than 0.05 parts by weight.

[0120] As the isocyanate crosslinking agent, a difunctional or higher isocyanate compound can be used, for example, aliphatic polyisocyanates such as trimethylene diisocyanate, butylene diisocyanate, hexamethylene diisocyanate (HDI), dimer acid diisocyanate, etc.; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate (IPDI), 1,3-bis(isocyanatomethyl)cyclohexane, etc.; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate (XDI), etc.; the above isocyanate compounds are linked to an allophanate bond, a biuret bond, an isocyanurate bond, a uretdione bond, a urea bond, a carbodiimide bond, a uretonimine bond, The polyisocyanate modified body obtained by modifying the diazinetrione bond, etc. As the example of commercial products, the following can be cited: trade name TAKENATE300S, TAKENATE500, TAKENATE600, TAKENATE D165N, TAKENATED178N (the above are manufactured by Takeda Pharmaceutical Industry Co., Ltd.), Sumidur T80, Sumidur L, Desmodur N3400 (the above are manufactured by Sumika Bayer Polyurethane Co., Ltd.), Millionate MR, Millionate MT, CORONATEL, CORONATEHL, CORONATEHX (the above are manufactured by Tosoh Corporation), etc. The isocyanate compound can be used alone or in combination of two or more. It is also possible to use a difunctional isocyanate compound and a trifunctional or higher isocyanate compound.

[0121] Examples of epoxy crosslinking agents include bisphenol A, epichlorohydrin type epoxy resins, ethylene glycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,6-hexanediol glycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, diamine glycidyl amine, N,N,N',N'-tetraglycidyl meta-xylylenediamine, and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane. These substances may be used alone or in combination of two or more.

[0122] As The oxazoline crosslinking agent can be used without particular limitation. Azoline-based substances.

[0123] Examples of aziridine crosslinking agents include trimethylolpropane tris[3-(1-aziridinyl)propionate] and trimethylolpropane tris[3-(2-methylaziridinyl)propionate].

[0124] As the carbodiimide crosslinking agent, a low molecular weight compound or a high molecular weight compound having two or more carbodiimide groups can be used.

[0125] The amount of cross-linking agent other than the multifunctional monomer is not particularly limited, and can be appropriately set in a manner to achieve the purpose of use of the cross-linking agent. Relative to 100 parts by weight of the monomer raw material, the amount of the above-mentioned cross-linking agent can be, for example, less than 10 parts by weight. In some embodiments, from the perspective of the softness of the cured product, it can be less than 5.0 parts by weight, less than 3.0 parts by weight, less than 2.0 parts by weight, less than 1.5 parts by weight, less than 1.0 parts by weight, less than 0.5 parts by weight, less than 0.2 parts by weight or less than 0.1 parts by weight. The lower limit of the amount of cross-linking agent other than the multifunctional monomer is not particularly limited. In some embodiments, from the perspective of appropriately exerting its use effect, relative to 100 parts by weight of the monomer raw material, the amount of the above-mentioned cross-linking agent can be, for example, more than 0.0001 parts by weight, more than 0.005 parts by weight, more than 0.01 parts by weight or more than 0.05 parts by weight.

[0126] (Other ingredients)

[0127] In addition, the curable composition disclosed herein may contain various additives (additives known in the field of adhesives) as needed, depending on the purpose and application. Examples of the above-mentioned additives include tackifying resins having a softening point of 60° C. or more, dyes, pigments and other colorants, antistatic agents, surfactants, surface lubricants, leveling agents, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, metal foils, etc. The additives may be used alone or in combination of two or more.

[0128] As examples of the above-mentioned tackifying resin (hereinafter, also referred to as "solid tackifying resin") having a softening point of 60°C or more, rosin tackifying resins, terpene tackifying resins, phenol tackifying resins, hydrocarbon tackifying resins, ketone tackifying resins, polyamide tackifying resins, epoxy tackifying resins, etc. having a softening point of 60°C or more can be cited. The solid tackifying resin is preferably soluble in the monomer raw material, and is typically included in the curable composition in the form of being dissolved in the liquid phase as a constituent component of the liquid phase. It is appropriate that the amount of the solid tackifying resin used is 30 parts by weight or less relative to 100 parts by weight of the monomer raw material. From the perspective of the transparency of the cured product, it is preferably 20 parts by weight or less, and can be 10 parts by weight or less, or 5 parts by weight or less. It is also possible not to use a solid tackifying resin.

[0129] In the curable composition disclosed herein, an acrylic oligomer may be contained as the above-mentioned other component as required from the viewpoint of improving adhesive strength, etc. As the above-mentioned acrylic oligomer, for example, an acrylic oligomer having a calculated Tg of about 20°C or more obtained based on the composition of the monomer raw material corresponding to the acrylic oligomer (i.e., the monomer raw material used as the synthetic raw material of the acrylic oligomer) can be used. It should be noted that the acrylic oligomer having a calculated Tg of X°C or more is usually solid (not liquid) at least at X°C.

[0130] In some embodiments, the calculated Tg of the acrylic oligomer is preferably above 25°C, more preferably above 30°C, may be above 40°C, may be above 50°C, may be above 60°C. From the viewpoint of improving adhesion and cohesion, it is advantageous for the calculated Tg of the acrylic oligomer to be above any of the above lower limits. On the other hand, there is no particular restriction on the upper limit of the calculated Tg of the acrylic oligomer. From the viewpoint of ease of preparation and compatibility of the curable composition, in some embodiments, it is appropriate to be below about 300°C. By calculating the Tg within the above range, a balance of properties can be achieved and adhesion can be appropriately improved.

[0131] The weight average molecular weight (Mw) of acrylic oligomers is typically greater than or equal to about 1000 and less than about 30000, preferably greater than or equal to about 1500 and less than about 20000, and more preferably greater than or equal to about 2000 and less than about 10000. By having Mw within the above range, good adhesive force and retention characteristics can be obtained, so it is preferred. The Mw of acrylic oligomers can be measured by gel permeation chromatography (GPC) and obtained as a standard polystyrene conversion value. Specifically, in HPLC8020 manufactured by Tosoh Corporation, TSKgelGMH-H (20) × 2 roots are used as columns and measured in tetrahydrofuran solvent at a flow rate of about 0.5 ml / min.

[0132] Examples of the monomers constituting the acrylic oligomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, and tert-butyl (meth)acrylate. Nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate and other chain alkyl (meth)acrylates; esters of (meth)acrylic acid and alicyclic alcohols such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrodicyclopentadienyl (meth)acrylate and other (meth)acrylates; aryl (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; (meth)acrylates obtained from terpene compound derivative alcohols, etc. Such (meth)acrylates can be used alone or in combination of two or more.

[0133] As the acrylic oligomer, from the viewpoint of further improving the adhesiveness of the adhesive layer, it is preferred that the monomer units be acrylic monomers having a relatively bulky structure represented by (meth)acrylic acid alkyl esters having a branched alkyl group such as isobutyl (meth)acrylate and tert-butyl (meth)acrylate; (meth)acrylic acid and alicyclic alcohol esters such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and tetrahydrodicyclopentadienyl (meth)acrylate; (meth)acrylic acid esters having a cyclic structure such as aryl (meth)acrylate such as phenyl (meth)acrylate and benzyl (meth)acrylate; etc. (for example, 10% by weight or more, 30% by weight or more, or 50% by weight or more of all monomer units of acrylic monomers having a relatively bulky structure). In addition, when ultraviolet rays are used during the synthesis of the acrylic oligomer and during the preparation of the adhesive layer, it is preferred that the substance having a saturated bond be used from the viewpoint of not causing polymerization hindrance, and (meth)acrylic acid alkyl esters having a branched alkyl group or esters with alicyclic alcohols can be preferably used as monomers constituting the acrylic oligomer.

[0134] From such a viewpoint, preferred acrylic oligomers include, for example, homopolymers of tetrahydrodicyclopentadienyl methacrylate (DCPMA), cyclohexyl methacrylate (CHMA), isobornyl methacrylate (IBXMA), isobornyl acrylate (IBXA), tetrahydrodicyclopentadienyl acrylate (DCPA), 1-adamantyl methacrylate (ADMA), and 1-adamantyl acrylate (ADA), copolymers of CHMA and isobutyl methacrylate (IBMA), copolymers of CHMA and IBXMA, copolymers of CHMA and acryloylmorpholine (ACMO), copolymers of CHMA and diethylacrylamide (DEAA), copolymers of ADA and methyl methacrylate (MMA), copolymers of DCPMA and IBXMA, and copolymers of DCPMA and MMA.

[0135] In the case of containing acrylic oligomer in the curable composition disclosed herein, its content is not particularly limited and can be appropriately set within the range of not significantly damaging the effect of the present invention. In some ways, relative to 100 parts by weight of the monomer raw material contained in the curable composition, the content of acrylic oligomer is about 20 parts by weight or less is appropriate, preferably about 15 parts by weight or less, more preferably about 10 parts by weight or less (e.g., about 5 parts by weight or less). The technology disclosed herein can preferably be implemented without using acrylic oligomer.

[0136] The curable composition disclosed herein can be manufactured by mixing the constituent materials of the curable composition in a manner such that the layered compound (A) is dispersed in the liquid phase. The above-mentioned curable composition can be manufactured, for example, by a method comprising mixing a liquid containing at least a portion of the components constituting the liquid phase of the curable composition with the layered compound (A). The above-mentioned liquid preferably contains a monomer raw material. The monomer raw material contained in the above-mentioned liquid can be a part of the entire monomer raw material used to manufacture the target object (curable composition), or it can be all. In the manner in which the above-mentioned liquid contains a part of the monomer raw material, the curable composition can be obtained by adding the remaining part of the monomer raw material at one time or in stages after mixing the above-mentioned liquid with the layered compound (A) and mixing.

[0137] From the viewpoint of the ease of dispersion of the layered compound (A), the above-mentioned liquid more preferably contains at least the polar monomer (m1) in the monomer raw material. The polar monomer (m1) contained in the above-mentioned liquid may be all or part of the polar monomer (m1) used to produce the target object. In the embodiment in which the monomer raw material contains monomers other than the polar monomer (m1), the monomers other than the polar monomer (m1) may be pre-included in the above-mentioned liquid together with the polar monomer (m1), may be mixed with the layered compound (A) at the same time as the liquid containing the polar monomer (m1), or may be added and mixed after the liquid containing the polar monomer (m1) and the layered compound (A) are mixed.

[0138] In some preferred embodiments, a curable composition (preferably a solvent-free curable composition) is manufactured by a method comprising mixing a layered compound (A) and a monomer raw material in the absence of a solvent. For example, it is preferred to mix a liquid containing a monomer raw material and substantially free of solvent with a layered compound (A) substantially free of solvent (in a dry state). The monomer raw material contained in the above-mentioned liquid can be a part of the entire monomer raw material used to manufacture the target (curable composition), or it can be all. In some embodiments, from the perspective of the ease of dispersion of the layered compound (A), the monomer raw material mixed with the layered compound (A) preferably contains a part or all of the polar monomer (m1) used to manufacture the target.

[0139] In a curable composition containing one or more constituent materials (e.g., a softener, a crosslinking agent, a polymerization initiator, etc.) in addition to the monomer raw material and the layered compound (A), each of the above constituent materials may be contained in the above liquid in advance, may be mixed with the layered compound (A) together with the above liquid, or may be added and mixed after the above liquid and the layered compound (A) are mixed. From the viewpoint of the ease of dispersion of the layered compound (A), in some embodiments, it is preferable to adopt a method in which other constituent materials are added and mixed simultaneously or sequentially after the layered compound (A) is mixed and dispersed with the monomer raw material.

[0140] In the curable composition disclosed herein, the monomer raw material includes a polar monomer (m1), so that the dispersion ease of the layered compound (A) in the liquid phase including the monomer raw material is good. Therefore, by mixing in the absence of a solvent, it is also possible to easily achieve a good dispersion state of the layered compound (A). Utilizing this, in some ways, the layered compound (A) is mixed with the monomer raw material (preferably mixed in the absence of a solvent) and the operation of dispersing the layered compound (A) can be implemented by using a shearing type disperser such as a disperser, a homogenizer, and a Three-One Motor and without applying ultrasonic waves. The above dispersion can be carried out under the conditions of more than 200rpm, more than 700rpm, more than 1200rpm, more than 1700rpm or more than 2000rpm, and in addition, for example, it can be carried out under the conditions of less than 12000rpm, less than 7000rpm, less than 4000rpm, less than 3000rpm or less than 2500rpm. In addition, the time for the above dispersion can be, for example, more than 3 minutes, more than 6 minutes, more than 9 minutes or more than 12 minutes, and, for example, less than 60 minutes, less than 45 minutes, less than 30 minutes or less than 20 minutes. From the perspectives of simplifying the device for manufacturing the curable composition, saving space, reducing energy costs, etc., it is advantageous not to apply ultrasound in order to disperse the layered compound (A). On the other hand, in some embodiments, auxiliary application of ultrasound for the purpose of promoting dispersion, etc. will not cause any hindrance.

[0141] <Composite Materials>

[0142] According to the present specification, a composite material as a cured product of any curable composition disclosed herein is provided. The composite material typically has a structure in which a layered compound (A) is dispersed in a matrix phase from a liquid phase of the curable composition. According to a curable composition in which the layered compound (A) is highly dispersed in the liquid phase, there is a tendency to form a composite material in which the layered compound (A) is more well dispersed in the matrix phase. From the viewpoint of improving the performance of the composite material, it is advantageous to improve the dispersibility of the layered compound (A) in the composite material.

[0143] The composite material can be formed by curing the curable composition disclosed herein by a suitable method (ultraviolet irradiation, heating, etc.). When the curing is performed by ultraviolet irradiation, the ultraviolet irradiation can be performed using a known high-pressure mercury lamp, low-pressure mercury lamp, metal halide lamp, etc.

[0144] (Film-like composite materials)

[0145] The composite material disclosed herein can also be formed into a film. The film-like composite material (hereinafter also referred to as "film-like solidified material") can be formed, for example, by curing the liquid film formed by the curable composition disclosed herein using an appropriate method (preferably using light or heat). The above-mentioned liquid film can be formed, for example, by coating. As the coating method of the curable composition, various methods known in the past can be used. Specifically, for example, methods such as roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, scraper bar coating, blade coating, air knife coating, curtain coating, lip die coating, extrusion coating using a die coater, etc. can be cited.

[0146] The above-mentioned film-like solidified material may be adhesive or non-adhesive. Here, the adhesive film-like solidified material refers to the following film-like solidified material: according to JIS Z0237 (2009), a SUS304 stainless steel plate is used as an adherend, and 30 minutes after being pressed onto the adherend by making a 2kg roller reciprocate once under a measurement environment of 23°C, the peel strength when peeled off in a 180° direction under a pulling speed of 300mm / min is 0.1N / 25mm or more. Such an adhesive film-like solidified material can be regarded as an adhesive layer or an adhesive sheet (substrate-free adhesive sheet) composed of the adhesive layer.

[0147] The thickness of the above-mentioned film-like solidified material (such as adhesive layer) is not particularly limited, and can be, for example, about 1 μm to about 1000 μm. In some embodiments, the thickness of the above-mentioned film-like solidified material can be, for example, 5 μm or more, preferably 15 μm or more, more preferably 25 μm or more, 30 μm or more, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, or 90 μm or more. From the perspective of the barrier properties (such as gas barrier properties), impact absorption, and adhesive properties of the film-like solidified material, it is advantageous for the film-like solidified material to have a thickness above the prescribed value. On the other hand, from the perspective of the optical properties (such as light transmittance, haze) of the film-like solidified material, in some embodiments, the thickness of the above-mentioned film-like solidified material can be, for example, 700 μm or less, 500 μm or less, 400 μm or less, 300 μm or less, 200 μm or less, or 150 μm or less.

[0148] The haze value of the film-like solidified material (such as adhesive layer) disclosed herein is not particularly limited. The above haze value can be 100%, for example, it can be less than 70%, less than 50%, less than 30% or less than 20%. In some ways, considering the adaptability in optical use, the haze value of the above film-like solidified material (such as adhesive layer) is 10% or less (for example, less than 9.0%) It is appropriate, and it is advantageous to be less than 8.0%, preferably less than 5.0% (for example, less than 4.0%), more preferably less than 3.5%, further preferably less than 2.5%, can be less than 2.0%, can be less than 1.5%, can be less than 1.0%, can be less than 1.0%. In the film-like solidified material, the layered compound (A) is more highly dispersed, which can help reduce the haze of the film-like solidified material. The lower limit of the haze value of the film-like solidified material is not particularly limited, and from the viewpoint of improving transparency, the smaller the haze value, the more preferred. On the other hand, in some embodiments, considering the balance with other properties (barrier properties, etc.), the haze value can be, for example, 0.05% or more, 0.1% or more, 0.2% or more, 0.3% or more, or 0.4% or more.

[0149] Here, the "haze value" refers to the ratio of diffuse transmitted light to total transmitted light when the object to be measured is irradiated with visible light. It is also called turbidity value. The haze value can be expressed by the following formula.

[0150] Th(%)=Td / Tt×100

[0151] In the above formula, Th is the haze value (%), Td is the scattered light transmittance, and Tt is the total light transmittance. The haze value can be measured by the method described in the examples described below.

[0152] The total light transmittance of the film-like cured product (e.g., adhesive layer) disclosed herein is not particularly limited. The above-mentioned total light transmittance may be 0%, for example, it may be 5% or more, 10% or more, 20% or more, 30% or more, or 40% or more. In some embodiments, considering the adaptability in optical applications, it is appropriate that the above-mentioned total light transmittance is greater than 50%, preferably 70% or more, preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. Theoretically, the upper limit of the total light transmittance is the value obtained by removing the light loss (Fresnel loss) caused by reflection generated at the air interface from 100%, which can be practically about 98% or less. Considering the balance with other properties (e.g., barrier properties), it can be about 95% or less, about 94% or less, or about 92% or less. The total light transmittance is measured according to JISK7136:2000 using a commercially available transmittance meter. As a transmittance meter, the trade name "HAZEMETER HM-150" manufactured by Murakami Color Technology Research Institute or its equivalent is used. More specifically, for example, the total light transmittance can be measured according to the examples described later.

[0153] The film-like cured product (e.g., adhesive layer) disclosed herein can exhibit good gas barrier properties by having a structure in which the layered cured product (A) is dispersed in the matrix phase of the cured product in the form of plate-like particles typically separated between the layered cured product (A). In some embodiments, the moisture permeability (unit: g / m 2 ·24 hours, the same below) can be, for example, 350 or less, 300 or less is advantageous, preferably 200 or less, more preferably 100 or less (for example, less than 100), can be 70 or less, can be 60 or less, and can also be 50 or less.

[0154] In some embodiments of the film-like solidified material disclosed herein, the film-like solidified material preferably satisfies any of the above-mentioned moisture permeability and the haze is less than 10%. Generally, when the content of the layered solidified material (A) in the film-like solidified material is increased, there is a tendency for its moisture permeability to decrease. On the other hand, when the content of the layered solidified material (A) in the film-like solidified material is increased, there is a tendency for its transparency (such as haze) to decrease. That is, low moisture permeability and high transparency are essentially in a compromise relationship. According to the technology disclosed herein, by improving the dispersibility of the layered compound (A) in the solidified material, compared with the solidified material with lower dispersibility of the layered compound (A), the reduction in transparency that occurs with the increase in the content of the layered solidified material (A) can be made gentle. Thus, a solidified material that balances low moisture permeability and high transparency can be achieved.

[0155] <Adhesive Sheet>

[0156] According to this specification, a film-like cured product of any curable composition disclosed herein, i.e., an adhesive layer and an adhesive sheet comprising the adhesive layer are provided. The above-mentioned adhesive sheet can be an adhesive sheet with a substrate having a form of an adhesive layer on one or both sides of a non-peelable substrate (support substrate), or can be an adhesive sheet without a substrate (i.e., an adhesive sheet without a non-peelable substrate, typically an adhesive sheet consisting of an adhesive layer) in which the above-mentioned adhesive layer is retained by a release liner. The concept of the adhesive sheet mentioned here can include objects referred to as adhesive tapes, adhesive labels, adhesive films, etc. The adhesive sheet disclosed here can be in a roll shape or in a monolithic shape. Alternatively, it can be an adhesive sheet further processed into a form of various shapes.

[0157] An example of the structure of the adhesive sheet disclosed herein is shown in Figure 1The adhesive sheet 1 is constituted as a single-sided adhesive sheet (single-sided adhesive sheet), and the single-sided adhesive sheet comprises: an adhesive layer (composite material) 10 whose first surface 10A serves as an attachment surface (adhesive surface) to an adherend, and a supporting substrate 20 laminated on a second surface 10B of the adhesive layer 10. The second surface 10B of the adhesive layer 10 is bonded to the first surface (non-releasable surface) 20A of the supporting substrate 20. As the supporting substrate 20, a plastic film such as a polyester film can be used. The supporting substrate 20 can be, for example, an optical film such as a polarizing plate. The adhesive sheet 1 before use (before being attached to an adherend) can be, for example, Figure 1 The adhesive sheet 50 with a release liner is shown in which the adhesive surface 10A is protected by a release liner 30 whose at least the adhesive layer side becomes a release surface (release surface). Alternatively, the second surface 20B (the surface on the opposite side of the first surface 20A, also referred to as the back side) of the supporting substrate 20 becomes the release surface, and the adhesive surface 10A is protected by winding or laminating in a manner that the adhesive surface 10A contacts the second surface 20B. The adhesive layer 10 can be a single-layer structure, or a laminated structure in which two or more sub-adhesive layers of different compositions are directly in contact (that is, not separated by a layer composed of a non-adhesive material) and laminated.

[0158] There are no particular limitations on the release liner, and for example, a release liner having a release-treated surface of a liner substrate such as a resin film or paper, a release liner having a low-adhesive material including a fluorine-containing polymer (polytetrafluoroethylene, etc.), a polyolefin resin (polyethylene, polypropylene, etc.), etc. can be used. For example, a release treatment agent such as polysiloxane or long-chain alkyl can be used for the release treatment. In some embodiments, a release-treated resin film can be preferably used as the release liner.

[0159] The adhesive sheet disclosed herein may be in the form of a substrate-free double-sided adhesive sheet composed of an adhesive layer. Figure 2 The figure shows a form in which the first surface (first adhesive surface) 10A and the second surface (second adhesive surface) 10B of the adhesive layer 10 are protected by release liners 31 and 32, at least the adhesive layer side of which serves as a releasable surface (release surface) before use. Alternatively, the back side (the surface opposite to the adhesive side) of the release liner 31 may serve as a release surface, and the adhesive surfaces 10A and 10B may be protected by winding or laminating in a manner such that the adhesive surface 10B contacts the back side of the release liner 31. Such a substrate-free double-sided adhesive sheet can be used, for example, by bonding a substrate (which may be an optical component such as an optical film) to at least one of the first adhesive surface and the second adhesive surface. The adhesive layer and the adhesive layer constituting the substrate-free double-sided adhesive sheet Figure 1The pressure-sensitive adhesive layer 10 in the pressure-sensitive adhesive sheet 1 shown may also have a single-layer structure or a laminated structure in which two or more sub-pressure-sensitive adhesive layers having different compositions are laminated in direct contact with each other.

[0160] The adhesive sheet disclosed herein may be a constituent element of an optical member with an adhesive sheet in which an optical member is bonded to one surface of an adhesive layer. For example, Figure 1 The adhesive sheet 1 shown may be Figure 3 The optical member 100 with an adhesive sheet is shown as a component of an optical member 70 bonded to one surface 10A of an adhesive layer 10. The optical member may be, for example, a glass plate, a resin film, a metal plate, or the like. Figure 1 In the PSA sheet 1 shown, when the supporting substrate 20 is an optical member such as an optical film, the PSA sheet 1 can be regarded as an optical member with a PSA sheet in which the optical member is bonded to the second surface 10B of the PSA layer 10 .

[0161] In addition, although not specifically shown in the figure, the adhesive sheet disclosed herein may also be in the form of a double-sided adhesive sheet with a substrate (double-sided adhesive sheet with a substrate) having a first side and a second side with non-peelable support substrate, a first adhesive layer fixedly laminated on the first side, and a second adhesive layer fixedly laminated on the second side. As examples of the configuration of such a double-sided adhesive sheet with a substrate, the following forms can be cited: Figure 1 In the single-sided adhesive sheet 1 shown, the second surface 20B of the supporting substrate 20 is a non-peelable surface and a second adhesive layer is provided on the second surface 20B, the second surface of the above-mentioned second adhesive layer is bonded to the second surface 20B of the supporting substrate 20, and the first surface (surface on the opposite side of the second surface) of the above-mentioned second adhesive layer becomes the second adhesive surface of the double-sided adhesive sheet with substrate. The composition of the adhesive constituting the second adhesive layer can be the same as the composition of the adhesive constituting the first adhesive layer, or it can be different. The double-sided adhesive sheet with substrate before use is the same as the above-mentioned substrate-free double-sided adhesive sheet, and can be a form in which the first adhesive surface and the second adhesive surface are protected by a release liner.

[0162] (Supporting substrate)

[0163] In the adhesive sheet having the form of a supporting substrate, the material of the supporting substrate (hereinafter sometimes referred to as "substrate") is not particularly limited and can be appropriately selected according to the purpose of use of the adhesive sheet, the mode of use, etc. As non-limiting examples of the substrate that can be used, there can be listed plastic films such as polyolefin films with polyolefins such as polypropylene (PP) and ethylene-propylene copolymer as the main component, polyester films with polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN) as the main component, and polyvinyl chloride films with polyvinyl chloride as the main component; foam sheets containing foams such as polyurethane foam, polyethylene (PE) foam, and polychloroprene foam; woven and non-woven fabrics formed by single or blended spinning of various fibrous materials (which can be natural fibers such as hemp and cotton; synthetic fibers such as polyester and vinylon; semi-synthetic fibers such as acetate, etc.); paper such as Japanese paper, high-quality paper, kraft paper, and crepe paper; metal foils such as aluminum foil and copper foil; etc. Examples of such composite substrates include substrates having a structure in which a metal foil and the above-mentioned plastic film are laminated, and plastic substrates reinforced with inorganic fibers such as glass cloth.

[0164] In some ways, various film substrates can be preferably used. The above-mentioned film substrate can be a porous substrate such as a foam film, a non-woven fabric sheet, or a non-porous substrate, or a substrate of a structure in which a porous layer and a non-porous layer are stacked. In some ways, as the above-mentioned film substrate, it is preferred to use a film substrate comprising a resin film that can independently maintain a shape (self-supporting or non-dependent) as a base film. Here, "resin film" refers to a non-porous structure, typically a resin film that is substantially free of bubbles (non-porous). Therefore, the above-mentioned resin film is a concept that is different from a foam film and a non-woven fabric. As the above-mentioned resin film, it is preferred to use a resin film that can independently maintain a shape (self-supporting or non-dependent). The above-mentioned resin film can be a single-layer structure, or it can be a multilayer structure (such as a three-layer structure) of more than two layers.

[0165] Examples of materials constituting the resin film include polyester resins mainly composed of polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); polyolefin resins mainly composed of polyolefins such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymers, and ethylene-butene copolymers; cellulose resins such as triacetyl cellulose, acetate resins, polysulfone resins, polyethersulfone resins, polycarbonate resins, polyamide (PA) resins such as nylon 6, nylon 66, and partially aromatic polyamides, and polyimides ( Cyclic polyolefin resins such as polyimide (PI) resins, transparent polyimide resins, polyamide-imide (PAI), polyetheretherketone (PEEK), polyethersulfone (PES), norbornene resins, (meth) acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, ethylene-vinyl acetate copolymer resins, ethylene-vinyl alcohol copolymer resins, polyarylate resins, polyphenylene sulfide (PPS) resins, polyurethane (PU), ethylene-vinyl acetate copolymer (EVA), polytetrafluoroethylene (PTFE), fluorinated polyimide and other fluorinated resins, etc.

[0166] The above-mentioned resin film can be a film formed by a resin material containing a single such resin, or a film formed by a resin material obtained by blending two or more. The above-mentioned resin film can be unstretched or stretched (e.g., uniaxially stretched or biaxially stretched). For example, PET film, PBT film, PEN film, unstretched polypropylene (CPP) film, biaxially stretched polypropylene (OPP) film, low-density polyethylene (LDPE) film, linear low-density polyethylene (LLDPE) film, PP / PE blended film, etc. can be preferably used. As an example of a preferred resin film from the viewpoint of strength and dimensional stability, PET film, PEN film, PPS film and PEEK film can be cited. From the viewpoint of ease of acquisition, PET film and PPS film are particularly preferred, wherein PET film is preferred.

[0167] As long as the effects of the present invention are not significantly impeded, known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, and anti-blocking agents may be added to the resin film as needed. The amount of the additives is not particularly limited and may be appropriately set according to the purpose of the adhesive sheet.

[0168] The method for producing the resin film is not particularly limited, and for example, a conventionally known general resin film forming method such as extrusion molding, inflation molding, T-die casting, calender roll molding, etc. can be appropriately adopted.

[0169] The substrate may be substantially composed of such a base film. Alternatively, the substrate may further include an auxiliary layer in addition to the base film. Examples of the auxiliary layer include an optical property adjustment layer (e.g., a coloring layer, an antireflection layer), a printed layer for imparting a desired appearance to the substrate, a laminated layer, an antistatic layer, a primer layer, a peeling layer, and other surface treatment layers.

[0170] In some embodiments, as a supporting substrate, a substrate with light transmittance (hereinafter also referred to as a light transmittance substrate) can be preferably used. Thus, a light-transmitting adhesive sheet with a substrate can be formed. The total light transmittance of the light-transmitting substrate can be, for example, greater than 50%, or can be greater than 70%. In some preferred embodiments, the total light transmittance of the supporting substrate is greater than 80%, more preferably greater than 90%, and can also be greater than 95% (for example, 95-100%). The above-mentioned total light transmittance is measured according to JIS K7136:2000 using a commercially available transmittance meter. As a transmittance meter, the trade name "HAZEMETER HM-150" manufactured by Murakami Color Technology Research Institute or its equivalent is used. As a preferred example of the above-mentioned light-transmitting substrate, a light-transmitting resin film can be listed. The above-mentioned light-transmitting substrate can be an optical film.

[0171] The thickness of the substrate is not particularly limited and can be selected according to the purpose of use and the mode of use of the adhesive sheet. The thickness of the substrate can be, for example, 500 μm or less. From the perspective of the operability and processability of the adhesive sheet, it is preferably 300 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 25 μm or less, or 10 μm or less. When the thickness of the substrate becomes smaller, there is a tendency to improve the followability of the surface shape of the adherend. In addition, from the perspectives of operability and processability, the thickness of the substrate can be, for example, 2 μm or more, 10 μm or more, or 25 μm or more.

[0172] For the surface of one side of the substrate to be laminated with the adhesive layer, corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, the formation of the primer layer by the coating of the primer (primer) and other previously known surface treatments can be implemented as needed. Such surface treatment can be a treatment for improving the anchoring of the adhesive layer to the substrate. The composition of the primer used in the formation of the primer layer is not particularly limited and can be appropriately selected from the known composition. The thickness of the primer layer is not particularly limited, and it is usually appropriate to be about 0.01 μm to about 1 μm, preferably about 0.1 μm to about 1 μm. As other treatments that can be implemented on the substrate as needed, antistatic layer formation treatment, coloring layer formation treatment, printing treatment, etc. can be listed. These treatments can be used alone or in combination.

[0173] (Peel Strength)

[0174] The adhesive sheet disclosed herein can show a peel strength of 0.1N / 25mm or more to the glass plate. The above-mentioned peel strength (peel strength to the glass plate) can be, for example, 0.2N / 25mm or more or greater than 0.2N / 25mm, preferably 0.5N / 25mm or more, more preferably 1.0N / 25mm or more, 1.5N / 25mm or more, 2.0N / 25mm or more, 3.0N / 25mm or more, 4.0N / 25mm or more, 5.0N / 25mm or more, 6.0N / 25mm or more. From the viewpoint of improving the peel strength to the glass plate, it may be advantageous to disperse the layered compound (A) more highly in the adhesive layer. There is no particular limit on the upper limit of the peel strength of the glass plate. In some embodiments, the peel strength to the glass plate can be, for example, less than 30N / 25mm, or less than 20N / 25mm.

[0175] The peel strength of the glass plate is determined as follows: the adhesive surface of the adhesive sheet to be measured is pressed against the glass plate by moving a 2kg rubber roller back and forth once, and the peel strength of the adhesive sheet when peeled off from the glass plate is measured using a tensile testing machine at 23°C and 50% RH according to JIS Z0237: 2000 at a peeling angle of 180 degrees and a pulling speed of 300 mm / min. Specifically, the measurement is performed by the method described in the embodiments described below. It should be noted that, depending on the composition of the adhesive sheet (for example, in the case of an adhesive sheet having a supporting substrate with sufficient strength, etc.), it is not necessary to use a PET film or the like for lining (reinforcement).

[0176] <Purpose>

[0177] In the curable composition disclosed herein, the layered compound (A) is typically dispersed in a liquid phase containing a monomer raw material in the form of plate-like particles formed by peeling the layered compound (A) between layers. Thus, the plate-like particles can function as a thickener that increases the viscosity of the curable composition. Properly increasing the viscosity of the curable composition can help improve the coating properties of the curable composition. For example, when the curable composition is applied thickly (for example, a thickness of more than 50 μm, more than 70 μm, etc.), from the perspective of improving the uniformity of the coating thickness (suppressing unevenness caused by flowing, dripping (drooping)), it is preferred that the viscosity of the curable composition is moderately high.

[0178] The composite material as a cured product of the curable composition disclosed herein can exhibit good barrier properties against gases such as water vapor and ammonia due to the contribution of the layered compound (A) dispersed (typically dispersed as plate-like particles) in the cured product. Utilizing this barrier property, the composite material can be used, for example, as a barrier material that protects an object from water vapor or other gases in the form of a film-like cured product.

[0179] In addition, in the composite material, the layered compound (A) is well dispersed, that is, uniformly dispersed (typically dispersed in the form of plate-like particles), which contributes to the improvement of thermal conductivity and electrical conductivity.

[0180] Furthermore, the composite material can be used for adsorption, retention, stabilization, etc. of target substances (eg, various functional substances) by utilizing the increase in surface area due to the dispersion of the layered compound (A) (typically, dispersion in the form of plate-like particles).

[0181] As can be understood from the above description and the following embodiments, matters disclosed by this specification include the following contents.

[0182] [1] A curable composition, wherein the curable composition comprises: a liquid phase containing a monomer raw material; and a layered compound dispersed in the liquid phase, wherein the layered compound is a layered compound that is organized using organic ions, and the monomer raw material contains a polar monomer (m1).

[0183] [2] The curable composition according to [1] above, wherein the monomer raw material contains a polar monomer (m1 N ).

[0184] [3] A curable composition according to the above [1] or [2], wherein the above-mentioned monomer raw material contains a (meth)acrylic acid chain alkyl ester (m2) having a chain alkyl group with 4 to 20 carbon atoms at the ester end, and the content of the above-mentioned (meth)acrylic acid chain alkyl ester (m2) in the above-mentioned monomer raw material is 55% by weight or more.

[0185] [4] The curable composition according to [3] above, wherein the monomer raw material contains a (meth)acrylic acid chain alkyl ester (m2 L ).

[0186] [5] The curable composition according to any one of [1] to [4] above, further comprising a softener.

[0187] [6] The curable composition according to any one of [1] to [5] above, wherein the curable composition is cured by at least one of light and heat to form an adhesive.

[0188] [7] A composite material, which is a cured product of the curable composition according to any one of [1] to [6] above.

[0189] [8] The composite material according to [7] above, wherein the composite material is formed into a film, and the moisture permeability (40°C, 92% RH) of the composite material is 300 g / m 2 Less than 24 hours, and the haze is less than 10%.

[0190] [9] The method for producing a curable composition according to any one of [1] to [6], wherein the method comprises mixing the layered compound and the monomer raw material in the absence of a solvent.

[0191] Example

[0192] Hereinafter, some embodiments of the present invention will be described, but the present invention is not intended to be limited to the contents shown in these specific examples. It should be noted that, unless otherwise specified, "parts" and "%" in the following description are weight references.

[0193] <Preparation of Curable Composition>

[0194] (Example 1)

[0195] 50 parts of isostearyl acrylate (ISTA) and 20 parts of an organized layered compound (trade name "Sumecton STN" manufactured by Kunimine Industries) were mixed by a stirrer (product name "ARV-310" manufactured by THINKY) at 2000 rpm for 15 minutes to obtain a dispersion. To the dispersion were added 50 parts of liquid polybutadiene as a softener (hydrogenated polybutadiene with hydroxyl groups at both ends, trade name "GI-1000", number average molecular weight 1500, manufactured by Nippon Soda Co., Ltd.), 0.07 parts of a crosslinking agent (trimethylolpropane triacrylate; hereinafter sometimes referred to as "TMPTA"), and 0.1 parts of a photoinitiator (trade name "Omnirad 184" and trade name "Omnirad 651" manufactured by IGM Resins Co., Ltd. were used in a weight ratio of 1:1), and the mixture was mixed at 2000 rpm for 15 minutes using the above-mentioned stirrer, and then centrifuged for degassing at 2200 rpm for 15 minutes to prepare the curable composition of this example.

[0196] (Example 2)

[0197] 47.5 parts of ISTA, 5 parts of N,N-dimethylacrylamide (DMAA) as a polar monomer, and 20 parts of the same organic layered compound as in Example 1 were mixed at 2000 rpm for 15 minutes using the above-mentioned stirrer to obtain a dispersion. 47.5 parts of the same softener as in Example 1, 0.07 parts of the same crosslinking agent as in Example 1, and 0.1 parts of the same photoinitiator as in Example 1 were added to the dispersion, mixed at 2000 rpm for 15 minutes, and then centrifuged and degassed at 2200 rpm for 15 minutes to prepare the curable composition of this example.

[0198] (Example 3~Example 5)

[0199] The curable compositions of each example were prepared in the same manner as in Example 2 except that the amount of ISTA used and the type and amount of the softener used were as shown in Table 1. It should be noted that in Table 1, GI-2000 and GI-3000 represent hydrogenated polybutadiene with hydroxy groups at both ends, manufactured by Nippon Soda Co., Ltd., trade name "GI-2000" (number average molecular weight 2000) and trade name "GI-3000" (number average molecular weight 3100), respectively.

[0200] (Example 6)

[0201] 47.5 parts of ISTA, 47.5 parts of 2-ethylhexyl acrylate (2EHA), 5 parts of DMAA and 20 parts of the same organic layered compound as in Example 1 were mixed at 2000 rpm for 15 minutes using the above-mentioned stirrer to obtain a dispersion. 0.07 parts of the same crosslinking agent as in Example 1 and 0.1 parts of the same photoinitiator as in Example 1 were added to the dispersion, mixed at 2000 rpm for 15 minutes using the above-mentioned stirrer, and then centrifuged and degassed at 2200 rpm for 15 minutes to prepare the curable composition of this example.

[0202] (Example 7)

[0203] 95 parts of 2EHA, 5 parts of DMAA and 23 parts of the same organic layered compound as in Example 1 were mixed at 2000 rpm for 15 minutes using the above-mentioned stirrer to obtain a dispersion. 0.07 parts of the same crosslinking agent as in Example 1 and 0.1 parts of the same photoinitiator as in Example 1 were added to the dispersion, mixed at 2000 rpm for 15 minutes using the above-mentioned stirrer, and then centrifuged and degassed at 2200 rpm for 15 minutes to prepare the curable composition of this example.

[0204] (Example 8)

[0205] Except having set the usage-amount of 2EHA and DMAA as shown in Table 1, it carried out similarly to Example 7, and prepared the curable composition of this example.

[0206] (Example 9)

[0207] A curable composition of this example was prepared in the same manner as in Example 7 except that N-vinylpyrrolidone (NVP) was used instead of DMAA.

[0208] <Preparation of laminated sheets>

[0209] The curable composition of each example was applied to a release film having a thickness of 38 μm and a release surface treated with a polysiloxane release agent on one side of a polyethylene terephthalate (PET) film so that the final thickness reached 100 μm, thereby forming a coating layer. A release film having a thickness of 38 μm and a release surface treated with a polysiloxane release agent on one side of a PET film so that the release surface of the film became the coating layer side was covered on the coating layer, thereby isolating the coating layer from oxygen. Next, a chemical lamp (manufactured by Toshiba Corporation) was used to irradiate at an illumination of 2.4 mW / cm 2 The coating layer was cured by applying ultraviolet light for 960 seconds. By doing so, a laminated sheet having a three-layer structure of the PET film was obtained by laminating the first and second surfaces of the composite material layer (adhesive layer) of the ultraviolet cured product of the coating layer.

[0210] The above-mentioned illuminance values ​​are measured based on an industrial UV tester (manufactured by TOPCON, trade name “UVR-T1”, light receiving unit model UD-T36) having a peak sensitivity wavelength of about 350 nm.

[0211] <Measurement and Evaluation>

[0212] (Total transmittance and haze value)

[0213] A test piece was prepared by bonding the adhesive layer of each example to an alkali-free glass (thickness 0.8 mm to 1.0 mm, total light transmittance 92%, haze 0.4%), and the total light transmittance and haze of the test piece were measured using a haze meter (manufactured by Murakami Color Research Institute, trade name "HAZEMETER HM-150") under a measurement environment of 23°C according to JIS K7136:2000. The values ​​obtained by subtracting the total light transmittance and haze of the alkali-free glass from the measured values ​​were taken as the total light transmittance (light transmittance) [%] and haze [%] of the adhesive layer. The results are shown in Table 1.

[0214] (Peel Strength)

[0215] Under the measuring environment of 23°C and 50%RH, a release film was peeled off from the laminated sheet of each example, and a PET film with a thickness of 50μm was attached to the exposed adhesive layer for lining, and then it was cut into a size of 25mm wide and 100mm long as a test piece. Another release film was peeled off from the test piece to expose the adhesive layer, and the surface of the alkaline glass plate (manufactured by Matsunami Glass Industries, Ltd., with a thickness of 1.35mm and a frosted blue plate) as the adherend was crimped by moving a 2kg roller back and forth once. After leaving it under the same environment for 30 minutes, a universal tensile compression tester was used to measure the peel strength [N / 25mm] under the conditions of a peeling angle of 180 degrees and a pulling speed of 300mm / min according to JIS Z0237:2000. As a universal tensile compression tester, a "tensile compression tester, TG-1kN" manufactured by Minebea was used. The results are shown in Table 1.

[0216]

[0217] As shown in Table 1, among the curable compositions of Examples 1 to 9 prepared without using an organic solvent and without providing ultrasonic treatment, the curable composition of Example 1 using a monomer raw material containing no polar monomer has a high haze of the cured product formed from the composition, and the dispersion of the layered compound is insufficient. In contrast, the curable compositions of Examples 2 to 9 using a monomer raw material containing DMAA or NVP as a polar monomer (m1) have a significantly lower haze than Example 1, although the content of the layered compound in the composition is equal to or more than that in Example 1, and a cured product with good dispersion of the layered compound is formed.

[0218] (Moisture Permeability)

[0219] The moisture permeability in the thickness direction of the adhesive layer of Example 2 was evaluated by the moisture permeability test method (cup method) for moisture-proof packaging materials according to JIS Z0208. The measurement conditions were as follows: the adhesive layer was attached to a 40 μm thick triacetylcellulose (TAC) film at a temperature of 40°C and a humidity of 92% RH, and the measurement was performed with the release film removed. The results are shown in Table 2.

[0220] (Ammonia permeability)

[0221] The ammonia permeability in the thickness direction of the adhesive layer of Example 2 was determined by the following method. That is, a sample cut into a disc shape with a diameter of 20 mm was sandwiched between a diaphragm punched into a circle with a diameter of 10 mm in the center and set on a lid. 1 mL of a 1% ammonia solution was added to a 20 mL SHS (static headspace) vial and fixed with the above-mentioned lid, and the vial and 20 mL of the collected liquid (ultrapure water) were added to a polypropylene container and covered with a lid. After standing at room temperature (25°C) for 6 hours, the collected liquid was analyzed by ion chromatography (IC) to determine the ammonia permeability. The results are shown in Table 2.

[0222] As a reference example, the moisture permeability and ammonia permeability of a commercially available acrylic pressure-sensitive adhesive layer (optical substrate-free pressure-sensitive adhesive sheet, 100 μm thick. The pressure-sensitive adhesive layer does not contain a layered compound or other inorganic powder) were measured in the same manner.

[0223]

[0224] As shown in Table 2, it was confirmed that the pressure-sensitive adhesive layer of Example 2 in which the layered compound was well dispersed had significantly lower water vapor permeability and ammonia permeability than the pressure-sensitive adhesive layer of the reference example not containing the layered compound, and was excellent in gas barrier properties.

[0225] The moisture permeability of the adhesive layers of Examples 3 to 7 and 9 was measured in the same manner as in Example 2. The moisture permeability of Example 3 was 31 g / m 2 ·After 24 hours, the moisture permeability of Example 4 is 31g / m 2 After 24 hours, the moisture permeability of Example 5 is 29g / m 2 24 hours, all at 20g / m 2 24 hours~50g / m 2 24 hours (more specifically, 25g / m 2 ·More than 24 hours and 35g / m 2 ·24 hours or less). In addition, the moisture permeability of Example 6 is 96g / m 2 ·After 24 hours, the moisture permeability of Example 7 is 148g / m 2 ·After 24 hours, the moisture permeability of Example 9 is 146g / m 2 24 hours, all at 95g / m 2 24 hours~300g / m 2 24 hours (more specifically, 95g / m 2 ·More than 24 hours and 150g / m 2 ·24 hours or less).

[0226] Although specific examples of the present invention have been described in detail above, these are merely illustrative and do not limit the claims. The technology described in the claims includes various modifications and changes made to the specific examples described above.

[0227] Description of symbols

[0228] 1.2 Adhesive sheet

[0229] 10 Adhesive layer

[0230] 10A First surface (adhesive surface)

[0231] 10B Second surface

[0232] 20 Support substrate

[0233] 20A first side

[0234] 20B Second side (back side)

[0235] 30, 31, 32 release liner

[0236] 50 Adhesive sheets with release liner

[0237] 70 optical components

[0238] 100 Components with adhesive sheets

Claims

1. A curable composition, wherein: The curable composition comprises: a liquid phase comprising a monomer raw material; and a layered compound dispersed in the liquid phase, The layered compound is a layered compound that is organically modified using organic ions. The monomer raw material comprises a polar monomer (m1).

2. The curable composition according to claim 1, wherein The monomer raw material comprises a polar monomer containing a nitrogen atom (m1 N ).

3. The curable composition according to claim 1 or 2, wherein The monomer raw material contains a (meth)acrylic acid chain alkyl ester (m2) having a chain alkyl group having 4 to 20 carbon atoms at the ester terminal. The content of the (meth)acrylic acid chain alkyl ester (m2) in the monomer raw material is 55% by weight or more.

4. The curable composition according to claim 3, wherein The monomer raw material contains a (meth)acrylic acid chain alkyl ester (m2) having a chain alkyl group with 13 to 20 carbon atoms at the ester end. L ).

5. The curable composition according to claim 1 or 2, wherein The curable composition further includes a softener.

6. The curable composition according to claim 1 or 2, wherein The curable composition forms an adhesive by being cured using at least one of light and heat.

7. A composite material, wherein: The composite material is a cured product of the curable composition according to claim 1 or 2.

8. The composite material according to claim 7, wherein The composite material is formed into a film shape, The moisture permeability of the composite material (40°C, 92% RH) is 300 g / m 2 Less than 24 hours, and the haze is less than 10%.

9. A production method, which is a production method of the curable composition according to claim 1 or 2, wherein: The production method includes mixing the layered compound and the monomer raw material in the absence of a solvent.

Citation Information

Patent Citations

  • Clear adhesive composition and adhesive sheet thereof

    JP2003129020A

  • Transparent self-adhesive composition excellent in external shock-absorbing property

    JP2003183457A

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A

  • Treatment liquid, set of treatment liquid and ink, treatment liquid imparting device, image formation device, treatment liquid imparting method, and image formation method

    JP2022134093A